STUDI TENTANG BENTUK, FUNGSI, DAN MAKNA PAKAIAN ADAT PANGULU KANAGARIAN SUNGAI JANIAH KECAMATAN GUNUNG TALANG KABUPATEN SOLOK PROPINSI SUMATRA BARAT - URFI HANIFAH, Dra. Zubaidah, M. Sn, Dra.Zubaidah, M.Pd (Universitas Negeri Padang, 2015)
The purpose of this study is to describe design, function and meaning of traditional dress, Pangulu. This research used kualitative reseach metode with descriptive approach, by observing traditional dress of Pangulu in Kanagarian Sungai Janiah, Kecamatan Gunung Talang, Kabupaten Solok Propinsi Sumatra Barat. The data were taken by observing the traditional dress itself and getting information from informan. They are the pangulu, wali nagari, and the members of community. Those deta were prosessed and researched in the form of notes (image record), taken from the informan that have been interviewed, documentation and literature study. The finding of this research showed that traditional dress of Pangulu in kanagarian Sungai Janiah consist of deta, baju lapang, salendang, sarawa lapang (celana longgar), sesampiang, cawek (ikat pinggang), keris, tungkek (tongkat) dan tarompa (sendal). The characteristic of these stuff is in deta, wich was designed like gonjong rumah gadang. In edition, baju lapang and sarawa lapang with no motif traditional Minangkabau. The function of Pangulu’s traditional dress is as a protector, as a symbol of identity. Furthermore the social function of this dress as a connector among the members of community. The traditional dress of Pangulu also has a meaningful with the rule of life of a Pangulu. It stuff of Pangulu traditional dress has a meaning as a symbol of the role of pangulu itself; a symbol of attitude and prohibition as a pangulu.Kata kunci : Makna, Pakaian Adat, Pangulu